Determination of patulin in apple juice by liquid chromatography-electrospray tandem mass spectrometry. Issue 1 (October 2021) - Radicevic, T; Jankovic, S; Simunovic, S; Stefanovic, S; Petrovic, Z; Jelusic, V
Abstract: Patulin is a mycotoxin produced by several fungi, ( Penicillium, Aspergillus, Byssochlamys) . The main sources of patulin intake in human diet are apples, apple juice and apple nectar, and for this reason, apple based foods are monitored for the presence of this mycotoxin. Commission Regulation EC No 1881/2006 lays down maximum residue limits (MRLs) of 50 µg/kg in apple juice and cider, 25 µg/kg in solid apple products, and 10 µg/kg in products for infants and young children. In Serbia, maximum permitted amounts of patulin in fruit juices, reconstituted concentrated fruit juices and fruit nectars, as well as in solid apple products, including apple compote and apple puree, intended for direct human consumption are prescribed in the Regulation on maximum concentrations of certain contaminants in foodstuffs. This paper presents the LC-MS/MS method for quantitative determination of patulin in apple juice. Criteria for method validation were taken from Commission Decision 2002/657/EC. Linearity was confirmed in the concentration ranges of 0-100 µg/kg, with the limit of detection (LoD) of 9.85 µg/kg. The performance of the method was successfully verified by participating in a proficiency study.